Integration of Raspberry Pi and Arduino for an Intelligent Medicine Dispensing System in Healthcare Facilities - Chinmay Prashant Tawde; Beena Ballal; Makarand Nagvekar; Mohammed Ahtesham Shaikh; Vaishnavi Phatkare (International Journal of Electrical Power and Machine Systems, 2024)
"Automatic Medicine Dispenser Using QR Code" revolutionizes healthcare service delivery by minimizing queue-related inconveniences. Our project created a vending machine using QR code technology in response to the evolving healthcare and technological landscape. The system is powered by an Arduino Mega 2560 and includes key components like a DC gear motor, L298N motor driver, infrared sensor, HC05 Bluetooth module, and a 12V power supply for drug delivery. The project comprises two teams, each dedicated to software and hardware development. On the software front, one system manages the Medicine Vending Machine (MVM) while the other generates doctor prescribed QR codes. Hardware components include Arduino Mega 2560, motors, IR sensors, Bluetooth modules, and more, facilitating precise medicine dispensing. Beyond conventional automation, the project tackles medicine unavailability. When a prescribed medicine is out of stock, the system promptly notifies the doctor. This real-time communication ensures that patients receive timely care, with doctors offering alternatives or new prescriptions. Challenges encompass handling diverse medicines, suggesting generics, managing inventory, and onboarding doctors. The project embodies a paradigm shift in healthcare, combining efficiency with patient- centric care.
Keywords: Arduino Mega; IOT; QR code; Smart Health Technology; Vending machines; Wireless Sensors; microcontrollers